THE DEVELOPMENT OF ISLAMIC CIVILISATION: FROM THE GOLDEN AGE TO THE PRESENT - Sabil Mokodenseho (Adisam Publisher, 2025)
Islamic civilisation has come a long way, from its golden age in the 8th to 14th centuries, when it was the world's centre of knowledge and innovation, to its current state of challenge but also potential. During the golden age, Islamic civilisation made significant contributions in the fields of science, mathematics, medicine and the arts. However, after this period, the Islamic world experienced setbacks due to internal and external factors such as political conflicts and colonisation. Nonetheless, the Muslim intellectual tradition survived and continues to be revived by new generations of scholars. Today, the Islamic world faces modern challenges but is also engaged in technological advancement, the global economy and intercultural dialogue. It is important for Muslim countries to continue reforms, innovations in education, and strengthen international collaboration in order to contribute significantly to the global community in the future.